Switching warfarin to direct oral anticoagulants in atrial fibrillation: Insights from the NCDR PINNACLE registry. Issue 7 (6th May 2020) - Sciria, Christopher T.; Maddox, Thomas M.; Marzec, Lucas; Rodwin, Benjamin; Virani, Salim S.; Annapureddy, Amarnath; Freeman, James V.; O'Hare, Ali; Liu, Yuyin; Song, Yang; Doros, Gheorghe; Zheng, Yue; et al.
Abstract: Background: Previous studies examining the use of direct oral anticoagulants (DOACs) in atrial fibrillation (AF) have largely focused on patients newly initiating therapy. Little is known about the prevalence/patterns of switching to DOACs among AF patients initially treated with warfarin. Hypothesis: To examine patterns of anticoagulation among patients chronically managed with warfarin upon the availability of DOACs and identify patient/practice‐level factors associated with switching from chronic warfarin therapy to a DOAC. Methods: Prospective cohort study of AF patients in the NCDR PINNACLE registry prescribed warfarin between May 1, 2008 and May 1, 2015. Patients were followed at least 1 year (median length of follow‐up 375 days, IQR 154‐375) through May 1, 2016 and stratified as follows: continued warfarin, switched to DOAC, or discontinued anticoagulation. To identify significant predictors of switching, a three‐level multivariable hierarchical regression was developed. Results: Among 383 008 AF patients initially prescribed warfarin, 16.3% (n = 62 620) switched to DOACs, 68.8% (n = 263 609) continued warfarin, and 14.8% (n = 56 779) discontinued anticoagulation. Among those switched, 37.6% received dabigatran, 37.0% rivaroxaban, 24.4% apixaban, and 1.0% edoxaban. Switched patients were more likely to be younger, women, white, and have private insurance (all P  < .001). Switching was less likely with increased stroke risk (OR, 0.92; 95%CI, 0.91‐0.93 per 1‐point increase CHA2 DS2 ‐VASc), but more likely with increased bleeding risk (OR, 1.12; 95%CI, 1.10‐1.13 per 1‐point increase HAS‐BLED). There was substantial variation at the practice‐level (MOR, 2.33; 95%CI, 2.12‐2.58) and among providers within the same practice (MOR, 1.46; 95%CI, 1.43‐1.49). Conclusions: Among AF patients treated with warfarin between October 1, 2010 and May 1, 2016, one in six were switched to DOACs, with differences across sociodemographic/clinical characteristics and substantial practice‐level variation. In the context of current guidelines which favor DOACs over warfarin, these findings help benchmark performance and identify areas of improvement.